Analisis Biaya Serta Percepatan Durasi Proyek Menggunakan Metode Crashing dengan Sistem Waktu Gilir Kerja dan Lembur (Studi Kasus: Puskesmas Wolowaru, Kabupaten Ende) - Made Widya Jayantari; I Made Aryatirta Predana; Yohanes Rikardus Wade (Reinforcement Review in Civil Engineering Studies and Management, 2022)
The construction of the Wolowaru Community Health Center in Ende Regency has been delayed. Delays in the duration of this project will have an impact on project costs which will get bigger. Therefore, an analysis of the accelerated duration of project implementation is needed so that the initial target can be achieved. This study applies the crashing method, namely speeding up the duration of each work item according to needs and calculations so as to avoid excessive delays. The application of this method is assisted by using the Microsoft Project 2013 with alternative working hours or overtime and work shift systems. The results of the analysis on the Wolowaru Community Health Center construction project in Ende Regency showed that the total project cost after carrying out an alternative of two hours of additional working hours was Rp. 8,371,332,720 and the duration of project implementation is 175 working days. This shows a fee that is 0.62% more expensive than the normal total cost and 20% faster than the normal duration. Then for the project cost after carrying out an alternative system of morning shifts and night shifts, it is Rp. 8,359,287,673 and the duration of project implementation is 156 working days. This shows a fee that is 0.48% more expensive than the normal total cost and 39% faster than the normal duration. From this study, it shows that the implementation of the work shift system requires cheaper costs with a shorter duration of work than the implementation of additional working hours in the Wolowaru Health Center development project in Ende Regency.